Green Recovery: Europe and the World - Robert Pollin (Intereconomics, 2020)
In Europe, and elsewhere, it is critical to recognize that this clean energy investment project will pay for itself in full over time in strictly financial terms – i.e. in addition to its obvious ecological benefits.
Keywords: 330; Klimapolitik; EU-Umweltpolitik; EU-Staaten